2013
DOI: 10.2478/10004-1254-64-2013-2308
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antipatulin Activity of Gluconobacter Oxydans Isolated from Apple Surface

Abstract: Fungicides are the most common agents used in postharvest treatment of fruit and are the most effective against blue mould, primarily caused by Penicillium expansum. Alternatively, blue mould can be treated with antagonistic microorganisms naturally occurring on fruit, such as the bacterium Gluconobacter oxydans. The aim of this study was to establish the antifungal potential of the G. oxydans 1J strain isolated from apple surface against Penicillium expansum in culture and apple juice and to compare it with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…In view of this, many researches have shown that some antagonist yeasts could directly inhibit the production of patulin. Through almost 30 years of research, dozens of yeasts, including Pichia caribbica [21], Rhodotorula glutinis [22], Pichia ohmeri [23], Rhodosporidium kratochvilovae [24], Gluconobacter oxydans [25], and several others have been shown to degrade patulin, and inhibited the growth of P. expansum . Coelho et al [26] reported that patulin concentration of 223 µg was decreased over 83% by P. ohmeri 158 cells when incubated at 25 °C for two days at a humidity >99.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, many researches have shown that some antagonist yeasts could directly inhibit the production of patulin. Through almost 30 years of research, dozens of yeasts, including Pichia caribbica [21], Rhodotorula glutinis [22], Pichia ohmeri [23], Rhodosporidium kratochvilovae [24], Gluconobacter oxydans [25], and several others have been shown to degrade patulin, and inhibited the growth of P. expansum . Coelho et al [26] reported that patulin concentration of 223 µg was decreased over 83% by P. ohmeri 158 cells when incubated at 25 °C for two days at a humidity >99.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the microorgan isms can not only inhibit fungal growth but can also reduce patulin levels in vitro. The biocontrol agents Pichia ohmeri (13), Rhodosporidium kratochvilovae (10), and Gluconobacter oxydans (7) are able to degrade patulin in medium or apple juice. In addition, lactic acid bacteria reduce patulin contamination by biological degradation (17) as well as by physical adsorption (18).…”
mentioning
confidence: 99%
“…The genera Stenotrophomonas and Gluconobacter were also abundant on the surface of apples in the orchard. They were isolated from bacterial communities within the soil ecosystem [ 61 , 62 ]. They both exhibited biocontrol activity against fruit rots.…”
Section: Discussionmentioning
confidence: 99%